Misallocation and Manufacturing TFP in Korea - Oh, JiYoon (2016)
This paper analyzes the effects of allocative efficiency on productivity in the manufacturing sector of Korea following Hsieh and Klenow (2009). The results of this research indicate that the overall allocative efficiency declined from 1990 to 2012. Using the method of Oberfield (2013), which allows inter-industry resource movement as well as intra-industry reallocation, we confirm that intensified misallocation generally results from intra-industry allocative inefficiency. The potential loss from instances of worsening misallocation is estimated to be approximately 0.6% points for each year, which is considerable in terms of the overall TFP. In terms of the firm size distribution, initially large establishments are more likely to expand if distortions are removed in most countries. One notable feature in Korea is that this pattern is pronounced. This implies that subsidies to unproductive small-sized establishments are heavily implemented.